Analysis of Risk Factors for Stunting Incidents in Posyandu, Hanopan Puskesmas Area, Arse District, South Tapanuli Regency, 2022 - Siregar, Mediawaty; Satria, Achmad Angga (PT Inovasi Pratama Internasional, 2024)
Stunting is a chronic nutritional problem caused by insufficient nutritional intake over a long period of time due to providing food that is not in accordance with nutritional needs (Millennium Challenge Account – Indonesia, 2018). Prevalence of stunting in Indonesia, the aim of this research is to analyze risk factors for stunting, such as: LBW. Maternal Education, Family Income, Environmental Sanitation Hygiene, further research can identify methods for promoting stunting prevention in Arse District. This research was conducted from August 2022 to August 2023 at the Posyandu in the Hanopan Community Health Center, Arse District, South Tapanuli Regency. The research design used a cross-sectional approach. The population in this study was 130 people. The sampling technique uses total sampling. Data was collected using height and weight measurements as well as questionnaires and analyzed using chi square with a significant value of <0.05. The results of this research show that there is an influence of education, family income, LBW, provision of clean water and healthy latrines on the risk of stunting at the Posyandu in the Hanopan Community Health Center area. The most dominant risk factor is LBW in related agencies, it is necessary to increase education regarding nutrition in children's growth and development, provide training on processing nutritious foods and foods that are unique and attractive to children.